Rancangan Video Pendidikan Pengguna Perpustakaan di Perpustakaan Universitas Negeri Padang - Refni, Azizah Raelsa; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
Writing this article aims; (1) to describe the process of making educational video library user in the UNP, (2) to describe video library user education as a medium for enhancing student understanding of the desert state university library services. Based on the analysis it can be concluded that the implementation of user education is conducted in Padang State University Libraries is less effective. This can be seen from there are still some students do not understand how to use the services available in the Library of the State University of Padang, especially in the online catalog and borrowing service. This lack of understanding is due at the time the student user education activities only a few participants who had the opportunity memperaktikkan online catalog services, while other participants see only just. Based on this conclusion suggested giving more interesting things in the delivery of user education materials to participants, so that participants do not feel bored, for example, just by using video media library user education. Keywords: design; video; education; library